Inactivation of Hepatitis A Virus and Human Norovirus in Clams Subjected to Heat Treatment - Fuentes, Cristina; Pérez-Rodríguez, Francisco J.; Sabrià, Aurora; Beguiristain, Nerea; Pintó, Rosa M.; Guix, Susana; Bosch, Albert (Frontiers in Microbiology, 2021)
Bivalve mollusk contamination by enteric viruses, especially human noroviruses (HuNoV) and hepatitis A virus (HAV), is a problem with health and economic implications. The aim of the study was the evaluation of the effect of heat treatment in clams (Tawera gayi) experimentally contaminated with HuNoV using a PMA-viability RTqPCR assay to minimize measurement of noninfectious viruses, and used HAV as a model to estimate infectivity loss. Spiked clams were immersed in water at 90ºC to ensure that internal meat temperature was maintained above 90ºC for at least 5 minutes. The treatment resulted in >3.89±0.24 log10 TCID50/g reduction of infectious HAV, confirming inactivation. For HuNoV, RTqPCR assays showed log10 reductions of 2.96±0.79 and 2.56±0.56, for GI and GII, respectively, and the use of PMA resulted in an additional log10 reduction for GII, providing a better correlation with risk reduction. In the absence of a cell culture system which could be used to determine HuNoV infectivity reduction, a performance criteria based on PMA-RTqPCR log reduction could be used to evaluate food product safety. According to data from this study, heat treatments of clams which cause reductions >3.5 log10 for GII as measured by PMA-RTqPCR assay may be regarded as an acceptable inactivation treatment, and could be set as a performance criterion to test the effectiveness of other time-temperature inactivation processes.